2014
DOI: 10.5152/jtgga.2013.79803
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of staging with preoperative parameters and frozen/section in patients with a preoperative diagnosis of grade 1 endometrioid tumor in endometrial cancer

Abstract: Objective:To investigate the likelihood of the detection of the necessity of staging preoperatively with the use of clinical parameters and frozen/ section (FS). Material and Methods:219 patients were included who were operated on between 1996 and 2010 with a diagnosis of grade 1 endometrioid adenocarcinoma in probe curettage. Results:Among the clinical characteristics, only age and body mass index (BMI) predicted staging preoperatively. The probability of staging increased as age increased and BMI decreased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
3
3
0
Order By: Relevance
“…Regarding the intraoperative gross and microscopic examination of the depth of myometrial invasion, it can be considered a relatively fast and accurate method, useful for identifying cancers at high risk for extrauterine metastases [17, 18]. With an 89.1% concordance rate between FS and PS regarding MI assessment, our study confirmed these results.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the intraoperative gross and microscopic examination of the depth of myometrial invasion, it can be considered a relatively fast and accurate method, useful for identifying cancers at high risk for extrauterine metastases [17, 18]. With an 89.1% concordance rate between FS and PS regarding MI assessment, our study confirmed these results.…”
Section: Discussionsupporting
confidence: 80%
“…1,4,[12][13][14] Karalok et al reported 5.9% of the cases with higher grade at the final diagnosis and 0.9% with a lower grade. 15 In our study, 7.7% of the cases had lower tumor grade and 15.5% had higher tumor grade at de-finitive diagnosis. Endometrioid carcinomas comprised 66.6% of these cases.…”
Section: Discussionsupporting
confidence: 44%
“…This involves transcriptional and post-transcriptional regulation of gene expression of immunesystem components and effector molecules (IL1-β, IL-6, IL-8 and TGF-β) [31,40,42,69,70,73] and of the vascular system, including early angiogenic targets, (i.e., PTGS/COX-2, VEGF and ELAVL1/HuR) [31,41,42,90]. In many cases, TIA1-mediated inflammatory responses have pathophysiological consequences associated with disorders such as arthritis, phagocytosis/autophagy, atherosclerosis, angiogenesis, neuroinflammation, obesity, myopathy, tauopathy and cancer [32,40,92,93,97,[128][129][130][131] (Figures 5 and 6). The pro-inflammatory cytokine TNF-α is a fundamental factor in the activation of proliferation and cytotoxicity, as well as in apoptosis.…”
Section: Inflammationmentioning
confidence: 99%
“…TNF-α is transcriptionally and post-transcriptionally regulated by TIA1, among other RBPs [40,68,69]. TNF-α is involved in many inflammatory processes in the body, including food allergies, rheumatic diseases such as arthritis or lupus, incompatibility in transplantation or difficulties in operations, as well as endometriosis due to cytokine regulation of endometrial stem cells, where TIA1 shows a differential and cyclic concentration [97,129,131]. Additionally, a TIA1-associated neuronal inflammatory phenotype has been described in tauopathies in the P301S mouse model mediated by a cytotoxic process of the central nervous system via TNF-α, IL-6 and IL1-β [97].…”
Section: Inflammationmentioning
confidence: 99%